Generative Artificial Intelligence Integration Yields Higher High School Poster Writing Performance : Integrasi Kecerdasan Buatan Generatif Menghasilkan Kinerja Menulis Poster Sekolah Menengah Atas Yang Tinggi - Salma Fauziyah; Jaja Wilsa; Ira Rahayu (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Educational transformations in the digital era increasingly leverage automated technologies to create interactive and adaptive instruction within language learning contexts. Specific Background In secondary education, environmental poster composition requires integrating persuasive text with visual communication, yet classroom instruction frequently relies on conventional methods lacking digital tool integration. Knowledge Gap Although standalone digital graphics software is utilized, quasi-experimental research simultaneously evaluating conversational artificial intelligence tools regarding student motivation and learning outcomes remains scarce. Aims This study evaluated ChatGPT as an artificial intelligence learning medium to determine its influence on student motivation, classroom engagement, and poster writing outcomes among eleventh-grade students. Results A quasi-experimental study employing a non-equivalent control group design revealed that the experimental class using ChatGPT achieved higher motivation scores, advancing from 58.88 to 70.71, compared to the control class moving from 54.00 to 60.59. Furthermore, learning outcomes in the experimental class rose from 64.71 to 91.18, significantly outperforming the control group which reached 83.24 (p = 0.000). Novelty This research provides empirical evidence that integrating conversational artificial intelligence into problem-based tasks accelerates creative ideation, persuasive drafting, and interactive learning behaviors beyond conventional group discussions. Implications Secondary school educators should integrate conversational artificial intelligence alongside teacher guidance to promote student-centered learning, heighten active participation, and elevate composition quality in language classrooms. Highlights ChatGPT deployment substantially elevates student motivation scores measured via the ARCS framework. Quasi-experimental analysis reveals significant cognitive assessment gains (p = 0.000) over conventional methods. Active classroom participation increases to 88.89% through structured prompt engineering and automated feedback. Keywords ChatGPT; Artificial Intelligence; Learning Motivation; Poster Writing; Learning Outcomes